Factors Influencing Student Intentions in Using the Mobile Legends Bang-Bang Game Using the UTAUT 2 and DeLone McLean Models - Nelly, Fredy Kusuma; Prasetiyo, Budi (Journal of Advances in Information Systems and Technology, 2023)
Online game users have increased every year following technological developments. This makes game developers develop their products even better so that they can play games on smartphones or commonly called mobile games. The increasing number of mobile game users is the backdrop for intense competition between game genres. However, one of the most frequently accessed games is Mobile Legends Bang-Bang. Then make the Mobile Legends game popular with various groups of students. Seeing this phenomenon, researchers are interested in researching Semarang State University students who play the online game Mobile Legend Bang-Bang because on campus there are many students who play together and form teams so that many E-Sport competitions are held. The UTAUT 2 and Delone & Mclean methods determine the factors that influence students' intentions to play the Mobile Legends Bang-Bang game. The data source in this study was taken from the results of online questionnaires so as to produce 316 respondent data after the screening process was carried out. Data processing uses SmartPLS V3 to test the outer and inner models. The results of this study indicate that of the ten hypotheses proposed, four hypotheses are not accepted. Namely, social influences on behavioral intentions, habits on behavioral intentions, system quality on behavioral intentions, and service quality on behavioral intentions. This means that social influence, habits, system quality, and service quality have no significant effect on behavioral intentions. The results of the analysis show that user intentions influence user behavioral in using the Mobile Legends Bang-Bang game.